Transient Oscillations Near the Dayside Open‐Closed Boundary: Evidence of Magnetopause Surface Mode?. Issue 11 (30th November 2019) - Kozyreva, O.; Pilipenko, V.; Lorentzen, D.; Baddeley, L.; Hartinger, M.
Abstract: Geomagnetic pulsations in Pc5‐6 band ( 3–20 min) are persistent feature of ULF activity at dayside high latitudes. Magnetopause surface eigenmodes may be suggested as potential mechanism of these pulsations. One might expect the ground response of these modes to be near ionospheric projection of the open‐closed field line boundary (OCB). Using data from instruments located at Svalbard we study transient geomagnetic response to impulsive "intrusion" of magnetosheath plasma into the dayside magnetosphere. These intrusions are triggered by modest changes of interplanetary magnetic field to southward, and observed as sudden shifts of equatorward red aurora boundary to lower latitudes and green line emission intensification. Each auroral disturbance is accompanied by burst of 1.7–2.0‐mHz geomagnetic pulsations. Near‐cusp latitudinal structure of ULF pulsations is compared with instant location of equatorward boundary of the red aurora, assumed to be a proxy of the OCB. Optical OCB latitude has been identified using data from the meridian scanning photometer. The latitudinal maximum of the transient geomagnetic response tends to be located near disturbed OCB proxy, within the error 1°–2° of the photometer and magnetometer methods. Recorded transient pulsations may be associated with the ground image of the magnetopause surface mode harmonic. Theoretical consideration indicates that after an initial excitation, surface large‐scale mode converts into localized Alfvén oscillations and thus can exist for limited time only. Therefore, MHD surface modes in realistic inhomogeneous plasma cannot be considered in isolation, but as a combined system of modes with discrete and continuous spectra with irreversible transformation between them. Key Points: Impulsive "intrusion" of magnetosheath plasma into dayside magnetosphere is accompanied by burst of geomagnetic 1.5 mHz pulsations Latitudinal maximum of transient magnetic response tends to be located near OCB optical proxy identified from meridian scanning photometer Dayside high latitude transient pulsations may be associated with the ground image of the magnetopause surface modes